Toxic Ingestion/Acute Iron (Fe) Ingestion - Mary Wittler; Jennifer Hannum (Association of American Medical Colleges, 2014)
Abstract Acute iron overdose is an uncommon but life-threatening ingestion that requires basic knowledge of clinical effects to evaluate and manage. This case requires residents to critically think about numerous tests and interventions to manage the case, including required laboratory studies, utility of radiographic studies, decontamination efforts, and antidote administration. Secondary to unfamiliarity with this ingestion, this case offers residents an opportunity to test their knowledge base and critically self-assess their approach to patient care for this ingestion. Included in the resource is the patient information (laboratory, EKG, and radiographic imaging) as well as a PowerPoint presentation.